Activity, patterns, and localization of carbonic acid enzymes in algae used in wastewater treatment. (Texas Journal of Engineering and Technology, 2022)
This article presents the results on the presence, activity, localization, properties and functional role of the carbonic anhydrase enzyme involved in the carbon metabolism of microalgae - euglena (which has a specific nutritional feature similar to heterotrophic and protozoa) Chlamydomonas and Dunaliella grown in intensive and mass culture, depending on the activity of various forms of carbonic anhydrase on the concentration of CO2 and nitrogen in the gas phase and medium. As analyzes have shown, all studied species and strains of algae have carbonic anhydrase activity, depending on the type of strain and cultivation conditions, 0,10-3,60 per mg of dry matter or 12-416 per chlorophyll unit. The lowest activity of the carbonic anhydrase enzyme was observed in the Dunalilla minute algae grown in an open-air semiproduction facility. In laboratory conditions grown in glass vessels, the minimum enzyme activity is observed in Chlamydomonas Reinhardii UA-5-16. The study of the localization of carbonic anhydrase in various cellular fractions of algae showed that in Dunaliella and Chlamydomonadal algae. The enzyme activity is mainly localized in the soluble fraction and gives similar values for both the homogeneous and the fraction of soluble proteins. In eugelena algae, a certain part (up to 40%) of carbonic anhydrase activity is localized in the membrane-bound fraction